Knowledge, Attitudes and Practices of Youths Towards the Intangible Cultural Heritage Elements of Dusun Ethnic in Malaysian Environment. Issue 1 (January 2022) - Juanis, B; Saleh, Y; Ghazali, M K A; Mahat, H; Hashim, M; Nayan, N; Hayati, R; Kurnia, R
Abstract: The continuity of the cultural heritage left by the previous generation is highly dependent on the new generation, especially the youth. Youth is a link to the legacy left behind. Therefore, this study aims to examine the extent of youths' knowledge, attitudes, and practices on the elements of the intangible cultural heritage of the Dusun ethnic group in Sabah, Malaysia. The research method used is quantitative with a survey research approach using a questionnaire instrument. The respondents consisted of 3 84 youths from the Dusun ethnic group aged 15 to 40 years. The data analysis methods used are descriptive and inferential analysis. The findings of the study showed that the level of knowledge of the intangible cultural heritage of the Dusun race among youths in Sabah for oral tradition (Moderate), lifestyle (High) and traditional dress (Moderate). Stages of oral tradition attitudes (High), lifestyle (High) and traditional clothing (High). Meanwhile, the level of practice of oral tradition (Moderate), lifestyle (Moderate) and traditional dress (Moderate). As for the analysis of differences, there is no significant difference for the variables of knowledge and practices of the intangible cultural heritage of the Dusun race between male and female youths. However, the attitude variables showed that there were significant differences between male and female youth. Pearson correlation analysis found a relationship between knowledge and attitude (Strong); knowledge with practice (Strong), and attitude with practice (Moderate). Implications from the study indicate that there are still variables that need improvement, especially in terms of knowledge. High knowledge is very important because it will affect the attitudes and practices of the youth.